Music to score automated music transcription - Castaneda, Marc Oliver R.; Galido, Adrian P.; Patal, Marvin H.; Salta, Christian N. (2000)
This paper discusses the design of a software system that accepts as input a digitized piano music recording. It then tries to derive the notes from the waveform so that the musical score could be produced. Various models of music transcription are discussed. The feasibility of the use of Short Time Fourier Transform is shown. It is a variant of Fourier Transform. Instead of getting the total frequency spectrum of the signal, we divide the signal into small sequential chunks to determine the spectral content at a specific period of time. The result is that the frequency spectrum is found at each short time. Successive spectra show the evolution of the change in frequency content during time. This is the most obvious method to use since musical instruments produce frequency components that change over time. As any other method, it has its inherent limitations. The choice of choosing a filter length L that will make a balanced trade-off between frequency resolution and time resolution is quite difficult. In the time domain, the ASDR event tracking (Attack, Sustain, Delay, Release) is used to track the spectral envelope of each note.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Musical notation -- Data processing; Music -- Data processing; Digital signal processing; Music transcription; Automated music transcription